2022
DOI: 10.1111/ntwe.12231
|View full text |Cite
|
Sign up to set email alerts
|

Information systems in nurses' work: Technical rationality versus an ethic of care

Abstract: Nurses increasingly interact with health information systems (HIS) in their daily work. This article examines how the problems that they confront in that interaction can be understood through the theoretical concepts of technical rationality and an ethic of care. The findings are based on a qualitative study of nurses in one Swedish hospital. They suggest that HIS did not support the holistic care of patients, and were not adapted to the varied and often urgent situations that nurses faced in their daily work,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Reports excluded: (n=7) Reason: not in line with inclusion criteria. relationships [23,28,30,32,[36][37][38] (n = 7). The remaining four articles presented different aims.…”
Section: Identification Of Studies Via Databases and Registersmentioning
confidence: 99%
See 4 more Smart Citations
“…Reports excluded: (n=7) Reason: not in line with inclusion criteria. relationships [23,28,30,32,[36][37][38] (n = 7). The remaining four articles presented different aims.…”
Section: Identification Of Studies Via Databases and Registersmentioning
confidence: 99%
“…Drawing on actor-network theory, they showed how technologies are an integrated (f)actor in present-day care practices, whereas both Townsend [38] and MacDonald et al [32] demonstrated how technological tools bring out relational and care ethical aspects in everyday practices and situations. Salminen-Karlsson and Golay [37] explored how professional healthcare workers experience tensions between care rationality and technical rationality as ethical dilemmas.…”
Section: Ethics Of Care As An Integrated Theoretical Framework and An...mentioning
confidence: 99%
See 3 more Smart Citations